Proximal femoral bionic nail—a novel internal fixation system for the treatment of femoral neck fractures: a finite element analysis - Ding, Kai; Zhu, Yanbin; Zhang, Yifan; Li, Yonglong; Wang, Haicheng; Li, Jiaxing; Chen, Wei; Zhang, Qi; Zhang, Yingze (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Currently, cannulated screws (CS) and dynamic hip screws (DHS) are widely used for the treatment of femoral neck fractures, but the postoperative complications associated with these internal fixations remain high. In response to this challenge, our team proposes a new approach involving triangular-supported fixation (TSF) and the development of the Proximal Femoral Bionic Nail (PFBN). The primary objective of this study is to investigate the biomechanical differences among CS, DHS, and PFBN in their capacity to stabilize femoral neck fractures. Methods: A normal proximal femur model was constructed according to the CT data of a normal healthy adult. A femoral neck fracture model was constructed and fixed with CS, DHS, and PFBN to simulate the fracture fixation model. The ABAQUS6.14 software was used to compare the biomechanical characters of the three fracture fixation models. Results: The maximum stresses and displacements of the normal proximal femur were 45.35MPa and 2.83mm, respectively. Under axial loading, PFBN was more effective than DHS and CS in improving the stress concentration of the internal fixation and reducing the peak values of von Mises stress, maximum principal stress and minimum principal stress. The PFBN fixation model exhibits superior overall and fracture section stability in comparison to both the DHS fixation model and the CS fixation model under axial loading. Notably, the maximum stress and peak displacement of PFBN and bone were lower than those of the DHS and CS fixation models under bending and torsional loading. Conclusion: PFBN shows considerable improvement in reducing stress concentration, propagating stress, and enhancing overall stability in the femoral neck fracture fixation model compared to DHS and CS. These enhancements more closely correspond to the tissue structure and biomechanical characteristics of the proximal femur, demonstrating that PFBN has great potential for therapeutic purposes in treating femoral neck fractures.